2013
DOI: 10.1111/jne.12007
|View full text |Cite
|
Sign up to set email alerts
|

17β‐Oestradiol Anti‐Inflammatory Effects in Primary Astrocytes Require Oestrogen Receptor β‐Mediated Neuroglobin Up‐Regulation

Abstract: Neuroglobin (Ngb), so named after its initial discovery in brain neurones, has received great attention as a result of its neuroprotective effects both in vitro and in vivo. Recently, we demonstrated that, in neurones, Ngb is a 17β-oestradiol (E(2) ) inducible protein that is pivotal for hormone-induced anti-apoptotic effects against H(2) O(2) toxicity. The involvement of Ngb in other brain cell populations, as well as in other neuroprotective effects of E(2) , is completely unknown at present. We demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 45 publications
4
84
0
4
Order By: Relevance
“…For each steroid receptor, strongly coexpressed genes within a brain region are likely related to the localized functional role of the receptor. For example, of the top 10 genes coexpressed with Esr1 across the whole brain, four were previously shown to be regulated by ESR1 and/or estrogens in various tissues (Gpr101, Calcr, Ngb, and Gpx3) (12)(13)(14)(15). These genes were also coexpressed with Esr1 in the HY, in line with their functional relationship to Esr1 in mediating, for example, reproductive and metabolic processes.…”
Section: Genes Spatially Coexpressed With Steroid Receptors Indicate mentioning
confidence: 68%
“…For each steroid receptor, strongly coexpressed genes within a brain region are likely related to the localized functional role of the receptor. For example, of the top 10 genes coexpressed with Esr1 across the whole brain, four were previously shown to be regulated by ESR1 and/or estrogens in various tissues (Gpr101, Calcr, Ngb, and Gpx3) (12)(13)(14)(15). These genes were also coexpressed with Esr1 in the HY, in line with their functional relationship to Esr1 in mediating, for example, reproductive and metabolic processes.…”
Section: Genes Spatially Coexpressed With Steroid Receptors Indicate mentioning
confidence: 68%
“…The current study demonstrated that 1-BP treatment decreased Ngb protein level in cerebral cortex in a dose-dependent manner. Ngb was expressed in neurons as well as astrocytes (De Marinis et al, 2013a, 2013b. Therefore, Ngb decrease induced by 1-BP made the cortical neurons more vulnerable to damage by reactive species and apoptosis which could cause neuron loss.…”
Section: Discussionmentioning
confidence: 97%
“…Ngb, firstly discovered in 2000, is expressed in neurons, astrocytes, retina and some endocrine tissues (Burmester et al, 2000;Burmester and Hankeln, 2004;De Marinis et al, 2013a). Brunori and Vallone (2007) demonstrated its highly conserved structure and function.…”
mentioning
confidence: 99%
“…It has been reported that the two classic receptors for estrogen, estrogen receptor α (ERα), and estrogen receptor β (ERβ) are closely related with inflammation [11][12][13]. In contrast to the long association of ERα with pain, the association of ERβ with pain may have a totally contradictory role to that mediated by ERα [14][15][16].…”
Section: Introductionmentioning
confidence: 99%